Audit Committee, Effectiveness, Bankruptcy Prediction, and Solvency Level Affect Audit Delay - Bramantio Adi Nugroho; Suripto Suripto; Effriyanti Effriyanti (GoAcademica Research & Publishing, 2021)
This study is to gather empirical evidence on the effectiveness of the Audit Committee, bankruptcy forecasts and audit delay solvency. Various manufacturing industries listed on the Indonesian Börse in 2015-2019 were among the population in this study. A selection from 11 companies with 55 observational data was obtained by using the purposeful sampling technique. Testing of hypotheses and the analyzes is conducted using Eviews-10 for the regression of panel data. The findings showed that the efficacy of the audit committee has no significant impact on audit delays, that bankruptcy predictions have a significant impact on the audit delay and that audit delays have a significant impact on the level of solvency.